1996
DOI: 10.1002/(sici)1097-0061(199605)12:6<541::aid-yea935>3.3.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of a Variant of Human Single‐Chain Urokinase‐Type Plasminogen Activator without an N‐Glycosylation Site in the Methylotrophic Yeast, Pichia pastoris and Characterization of the Secreted Product

Abstract: Human single-chain urokinase-type plasminogen activator without an N-glycosylation site (scu-PA-Q302) was produced in the methylotrophic yeast, Pichia pastoris using the shortened prepeptide sequence of a fungal aspartic proteinase, Mucor pusillus rennin (MPR). The level of urokinase-type plasminogen activator (u-PA) immunoreactive material in YPM medium was 0.47 mg/l; however, most of the secreted product had been processed to smaller polypeptides. The N-terminal amino acid sequence of major species was ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 35 publications
(46 reference statements)
1
12
0
Order By: Relevance
“…AOX1-deleted transformants could grow slowly in the methanol medium because they had another alcohol oxidase encoded by the AOX2 gene, which is expressed more weakly than the AOX1 gene . The frequency of AOX1 disruption by double crossing-over (37%) was identical to the frequency reported for the production of hepatitis B antigen by Cregg et al (1987), tumour necrosis factor by Sreekrishna et al (1989) and human single-chain urokinase-type plasminogen activator (Tsujikawa et al, 1996).…”
supporting
confidence: 77%
“…AOX1-deleted transformants could grow slowly in the methanol medium because they had another alcohol oxidase encoded by the AOX2 gene, which is expressed more weakly than the AOX1 gene . The frequency of AOX1 disruption by double crossing-over (37%) was identical to the frequency reported for the production of hepatitis B antigen by Cregg et al (1987), tumour necrosis factor by Sreekrishna et al (1989) and human single-chain urokinase-type plasminogen activator (Tsujikawa et al, 1996).…”
supporting
confidence: 77%
“…Because the pmr1‐ Δ mutation caused a defect of vacuolar protein sorting (see above), which could lead to an increased proteolytic activation of uPA (Agaphonov et al , 2005a), uPA‐Q 302 secreted by the pmr‐ Δ mutant and wild‐type control strain was analyzed by Western blotting. It was previously observed that buffering of the culture medium with ammonium phosphate decreased the proteolysis of uPA (Tsujikawa et al , 1996; Agaphonov et al , 2005a). Indeed, the major band of uPA‐Q 302 from the culture supernatants migrated in SDS‐PAGE as a ∼45‐kDa protein (the calculated molecular weight of uPA‐Q 302 is 46 kDa).…”
Section: Resultsmentioning
confidence: 99%
“…Although there is little information concerning the mechanism and speci¢city of O-glycosylation in P. pastoris, the presence of O-glycosylation has been reported in some heterologous proteins, such as the Aspergillus awamori glucoamylase catalytic domain [47], human IGF-1 [23], barley K-amylases 1 and 2 [48], and human single-chain urokinase-type plasminogen activator [49].…”
Section: O-linked Glycosylationmentioning
confidence: 99%